2021
DOI: 10.1021/acssuschemeng.1c00319
|View full text |Cite
|
Sign up to set email alerts
|

Facile Construction of a Hollow In2S3/Polymeric Carbon Nitride Heterojunction for Efficient Visible-Light-Driven CO2 Reduction

Abstract: The development of high-efficiency photocatalysts is of great importance to realize robust solar-driven CO2 conversion; however, the low carrier separation efficiency and poor light absorption ability usually limit the performance of the photocatalysts. Herein, a hollow In2S3/polymeric carbon nitride (IS/CN) heterojunction was prepared via electrostatic self-assembly and in situ sulfidation under solvothermal conditions. The intimate interfacial contact between the IS and CN facilitates the construction of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…In general, the E CB of an n-type semiconductor is 0–0.2 V more negative than its V fb . 68 Combined with the relationship E NHE / V = E Ag/AgCl / V + 0.197 V, the E CB values of DCN, DCN-S and DCCN-S are approximately −1.12, −0.74 and −1.05 V ( vs. NHE, pH = 7), respectively, in good agreement with those estimated from VB-XPS spectra. On the basis of the above analysis, the band structure alignments are illustrated in Fig.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In general, the E CB of an n-type semiconductor is 0–0.2 V more negative than its V fb . 68 Combined with the relationship E NHE / V = E Ag/AgCl / V + 0.197 V, the E CB values of DCN, DCN-S and DCCN-S are approximately −1.12, −0.74 and −1.05 V ( vs. NHE, pH = 7), respectively, in good agreement with those estimated from VB-XPS spectra. On the basis of the above analysis, the band structure alignments are illustrated in Fig.…”
Section: Resultssupporting
confidence: 75%
“…According to the formula E NHE / V = Φ + − 4.44 ( E NHE : the potential of the standard hydrogen electrode; Φ = 4.30 eV: the electron work function of the analyzer), the positions of the valence band maximum ( E VB ) for DCN, DCN-S and DCCN-S were estimated to be 1.69, 1.81 and 1.58 V ( vs. NHE, pH = 7), respectively. 68 Based on the relationship between E g and band edge positions, the positions of the conduction band minimum ( E CB ) of DCN, DCN-S and DCCN-S were estimated to be −1.12, −0.74 and −1.06 V ( vs. NHE, pH = 7), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…256,257 Hollow In 2 S 3 /polymeric carbon-nitride (IS/CN) heterojunctions were fabricated by in situ sulfidation under solvothermal conditions and electrostatic self-assembly. 258 Both IS and CN are stimulated by visible light irradiation, producing holes and electrons, with the electrons leaping into the conduction band (CB) and the holes remaining in the valence band (VB). Because of the resulting heterojunction, the photogenerated holes in the VB of the CN are transferred to the VB of the IS, while the photogenerated electrons in the CB of the IS are move to the CB of the CN.…”
Section: Mhcs Application Towards Co2 Utilizationmentioning
confidence: 99%
“…In 2012, Dong and Zhang first used pristine g-C 3 N 4 as an organic photocatalyst for CO 2 reduction . Since then, several research groups have further improved its photoactivity by incorporating metal components in g-C 3 N 4 . In addition, POPs have emerged as a promising semiconductor for photocatalytic reactions. In 2019, Dai et al reported two triphenylamine (TPA)-based porous polymers, 2,5-diphenyl-1,3,4-oxadiazole (OXD)-TPA and biphenyl (BP)-TPA; for these two polymers, the electron-withdrawing unit of OXD improved both the light-harvesting capability and charge separation efficiency .…”
Section: Introductionmentioning
confidence: 99%